# ListT done right

### From HaskellWiki

m |
(Remove an extra 'where' keyword.) |

## Revision as of 15:18, 1 March 2009

## Contents |

## 1 Introduction

The Haskell hierarchical libraries implement a ListT monad transformer. There are, however, some problems with that implementation.

- imposes unnecessary strictness.ListT
- isn't really a monad transformer, ie.ListTisn't always a monad for a monadListT m.m

See the #Examples below for demonstrations of these problems.

## 2 Implementation

The following implementation tries to provide a replacement for the ListT transformer using the following technique. Instead of associating a monadic side effect with a list of values (There is also a ListT done right alternative.

import Data.Maybe import Control.Monad.State import Control.Monad.Reader import Control.Monad.Error import Control.Monad.Cont -- The monadic list type data MList' m a = MNil | a `MCons` MList m a type MList m a = m (MList' m a) -- This can be directly used as a monad transformer newtype ListT m a = ListT { runListT :: MList m a } -- A "lazy" run function, which only calculates the first solution. runListT' :: Functor m => ListT m a -> m (Maybe (a, ListT m a)) runListT' (ListT m) = fmap g m where g MNil = Nothing g (x `MCons` xs) = Just (x, ListT xs) -- In ListT from Control.Monad this one is the data constructor ListT, so sadly, this code can't be a drop-in replacement. liftList :: Monad m => [a] -> ListT m a liftList [] = ListT $ return MNil liftList (x:xs) = ListT . return $ x `MCons` (runListT $ liftList xs) instance Functor m => Functor (ListT m) where fmap f (ListT m) = ListT $ fmap (fmap f) m instance Functor m => Functor (MList' m) where fmap _ MNil = MNil fmap f (x `MCons` xs) = f x `MCons` fmap (fmap f) xs -- Why on earth isn't Monad declared `class Functor m => Monad m'? -- I assume that a monad is always a functor, so the contexts -- get a little larger than actually necessary instance (Functor m, Monad m) => Monad (ListT m) where return x = ListT . return $ x `MCons` return MNil m >>= f = joinListT $ fmap f m instance MonadTrans ListT where lift = ListT . liftM (`MCons` return MNil) instance (Functor m, Monad m) => MonadPlus (ListT m) where mzero = liftList [] (ListT xs) `mplus` (ListT ys) = ListT $ xs `mAppend` ys -- Implemenation of join joinListT :: (Functor m, Monad m) => ListT m (ListT m a) -> ListT m a joinListT (ListT xss) = ListT . joinMList $ fmap (fmap runListT) xss joinMList :: (Functor m, Monad m) => MList m (MList m a) -> MList m a joinMList = (=<<) joinMList' joinMList' :: (Functor m, Monad m) => MList' m (MList m a) -> MList m a joinMList' MNil = return MNil joinMList' (x `MCons` xs) = x `mAppend` joinMList xs mAppend :: (Functor m, Monad m) => MList m a -> MList m a -> MList m a mAppend xs ys = (`mAppend'` ys) =<< xs mAppend' :: (Functor m, Monad m) => MList' m a -> MList m a -> MList m a mAppend' MNil ys = ys mAppend' (x `MCons` xs) ys = return $ x `MCons` mAppend xs ys -- These things typecheck, but I haven't made sure what they do is sensible. -- (callCC almost certainly has to be changed in the same way as throwError) instance (MonadIO m, Functor m) => MonadIO (ListT m) where liftIO = lift . liftIO instance (MonadReader s m, Functor m) => MonadReader s (ListT m) where ask = lift ask local f = ListT . local f . runListT instance (MonadState s m, Functor m) => MonadState s (ListT m) where get = lift get put = lift . put instance (MonadCont m, Functor m) => MonadCont (ListT m) where callCC f = ListT $ callCC $ \c -> runListT . f $ \a -> ListT . c $ a `MCons` return MNil instance (MonadError e m, Functor m) => MonadError e (ListT m) where throwError = lift . throwError {- This (perhaps more straightforward) implementation has the disadvantage that it only catches errors that occur at the first position of the list. m `catchError` h = ListT $ runListT m `catchError` \e -> runListT (h e) -} -- This is better because errors are caught everywhere in the list. (m :: ListT m a) `catchError` h = ListT . deepCatch . runListT $ m where deepCatch :: MList m a -> MList m a deepCatch ml = fmap deepCatch' ml `catchError` \e -> runListT (h e) deepCatch' :: MList' m a -> MList' m a deepCatch' MNil = MNil deepCatch' (x `MCons` xs) = x `MCons` deepCatch xs

## 3 Examples

Here are some examples that show why the old ListT is not right, and how to use the new ListT instead.

### 3.1 Sum of squares

Here's a silly example how to use ListT. It checks if anmyTest :: Int -> ListT IO (Int, Int) myTest n = do let squares = liftList . takeWhile (<=n) $ map (^(2::Int)) [0..] x <- squares y <- squares lift $ print (x,y) guard $ x + y == n lift $ putStrLn "Sum of squares." return (x,y) runMyTest :: Int -> IO (Int, Int) runMyTest = fmap (fst . fromJust) . runListT' . myTest

*Main> runMyTest 5 (0,0) (0,1) (0,4) (1,0) (1,1) (1,4) Sum of squares. *Main> runMyTest' 5 (0,0) (0,1) (0,4) (1,0) (1,1) (1,4) Sum of squares. (4,0) (4,1) Sum of squares. (4,4)

### 3.2 Grouping effects

I didn't understand the statement "after I understood why it is too strict. I found the answer in Composing Monads. It's in

fact a direct consequence of the unnecessary strictness.not associative (which is one of the monad laws), because grouping affects when side effects are run (which may in turn affect the answers). Consider

import Control.Monad.List import Data.IORef test1 :: ListT IO Int test1 = do r <- liftIO (newIORef 0) (next r `mplus` next r >> next r `mplus` next r) >> next r `mplus` next r test2 :: ListT IO Int test2 = do r <- liftIO (newIORef 0) next r `mplus` next r >> (next r `mplus` next r >> next r `mplus` next r) next :: IORef Int -> ListT IO Int next r = liftIO $ do x <- readIORef r writeIORef r (x+1) return x

Under Control.Monad.List.ListT, test1 returns the answers

### 3.3 Order of printing

Here is another (simpler?) example showing why "a,b,c :: ListT IO () [a,b,c] = map (liftIO . putChar) ['a','b','c'] t1 :: ListT IO () t1 = (a `mplus` a >> b) >> c t2 :: ListT IO () t2 = a `mplus` a >> (b >> c)

## 4 Relation to Nondet

NonDeterminism describes another monad transformer that can also be used to model nondeterminism. In fact,toListT :: (Monad m) => NondetT m a -> ListT m a toListT (NondetT fold) = ListT $ fold ((return.) . MCons) (return MNil) toNondetT :: (Monad m) => ListT m a -> NondetT m a toNondetT (ListT ml) = NondetT (\c n -> fold c n ml) where fold :: Monad m => (a -> m b -> m b) -> m b -> MList m a -> m b fold c n xs = fold' c n =<< xs fold' :: Monad m => (a -> m b -> m b) -> m b -> MList' m a -> m b fold' _ n MNil = n fold' c n (x `MCons` xs) = c x (fold c n xs)

*I propose to replace every occurence of `fmap` in the above code with `liftM`, thereby moving `class Functor` and the complaint about it not being a superclass of `Monad` completely out of the picture. I'd simply do it, if there wasn't this feeling that I have overlooked something obvious. What is it? -- Udo Stenzel*

There's no particular reason why I used fmap, except that the page has the (unfortunate!) title "ListT Done Right", and having Functor superclass of Monad certainly is the right thing. But I agree, that mistake has long been done and I feel my half-hearted cure is worse than the disease. You can find an alternative, more concise definition of a ListT transformer based on even-style lists here: ListT done right alternative

amb has AmbT, which could be considered as 'ListT done right' (since Amb is identical to the list monad).